Analysis of cyanobacterial metabolites in surface and raw drinking waters reveals more than microcystin. (1st September 2018) - Beversdorf, Lucas J.; Rude, Kayla; Weirich, Chelsea A.; Bartlett, Sarah L.; Seaman, Mary; Kozik, Christine; Biese, Peter; Gosz, Timothy; Suha, Michael; Stempa, Christopher; Shaw, Christopher; Hedman, Curtis; et al.
Abstract: Freshwater cyanobacterial blooms are becoming increasingly problematic in regions that rely on surface waters for drinking water production. Microcystins (MCs) are toxic peptides produced by multiple cyanobacterial genera with a global occurrence. Cyanobacteria also produce a variety of other toxic and/or otherwise bioactive peptides (TBPs) that have gained less attention including cyanopeptolins (Cpts), anabaenopeptins (Apts), and microginins (Mgn). In this study, we compared temporal and spatial trends of four MCs (MCLR, MCRR, MCYR, MCLA), three Cpts (Cpt1020, Cpt1041, Cpt1007), two Apts (AptF, AptB), and Mgn690 in raw drinking water and at six surface water locations above these drinking water intakes in a eutrophic lake. All four MC congeners and five of six TBPs were detected in lake and raw drinking water. Across all samples, MCLR was the most frequently detected metabolite (100% of samples) followed by MCRR (97%) > Cpt1007 (74%) > MCYR (69%) > AptF (67%) > MCLA (61%) > AptB (54%) > Mgn690 (29%) and Cpt1041 (15%). Mean concentrations of MCs, Apts, and Cpts into two drinking water intakes were 3.9 ± 4.7, 0.14 ± 0.21, and 0.38 ± 0.92, respectively. Mean concentrations in surface water were significantly higher ( p  < 0.05) than in drinking water intakes for MCs but not for Cpts and Apts. Temporal trends in MCs, Cpts, and Apts in the two raw drinking water intakes were significantly correlated ( p  < 0.05) with measures of cell abundance (chlorophyll- a, Microcystis cell density), UV absorbance, and turbidity in surface water. This study expands current information about cyanobacterial TBPs that occur in lakes and that enter drinking water treatment plants and underscores the need to determine the fate of less studied cyanobacterial metabolites during drinking water treatment that may exacerbate toxicity of more well-known cyanobacterial toxins. Graphical abstract: Image 1 Highlights: We measured four MCs and six TBPs in lake and raw drinking water. Nine TBPs were detected in both lake and raw drinking water. Loading of some TBPs to raw drinking water was comparable to MCs. Measures of cell abundance, absorbance and turbidity significantly correlate to peptides in raw drinking water.